Digital health determinants & divide in the Arab world: A cross-sectional study - Radwan Qasrawi; Reema Tayyem; Suliman Thwib; Ghada Issa; Malak Amro; Razan AbuGhoush; Haleama Al Sabbah; Khlood Bookari; Noor Alawadhi; Sabika Allehdan; Hana Trigui; Elie Sokhn; et al. (PLoS ONE, 2025)
Background Digital determinants of health include key technological factors such as internet access, digital literacy, and the quality of online health information. These elements critically influence health outcomes and behaviors. Methods This study examined the impact of digital health determinants on health improvement across ten Arab countries: Bahrain, Palestine, Lebanon, Jordan, Kuwait, the United Arab Emirates, Saudi Arabia, Egypt, Morocco, and Tunisia. The study analyzed a dataset of 12,522 samples after implementing SMOTE-ENN to balance underrepresented demographics, capturing data on digital literacy, internet access, and the impact of online health information on personal health. Results Results showed that 93.9% of participants reported having internet access, yet 71.4% did not receive formal education on internet usage. Morocco, Tunisia, and Jordan reported the highest percentages of individuals without such education. Regarding health impacts, 32.9% of participants reported significant personal health improvements linked to digital determinants. Egypt, Lebanon, and Saudi Arabia had higher rates of positive health impacts, while Morocco, Jordan, and Bahrain reported the lowest health improvements. Higher digital literacy and reliable internet access were positively associated with better health outcomes across all countries, whereas specific sociodemographic and digital factors varied: younger age and urban residence were linked to greater benefit in the Gulf; education level and healthcare access were especially influential in North Africa; and in the Levant, digital literacy and use of trusted health sources showed strong impact. These findings show both shared and region-specific drivers of digital health benefits. Conclusion Improving health outcomes requires diversification: foundational education on internet usage must be combined with broader digital literacy initiatives, efforts to build and maintain trust in credible online health platforms, and strategies that actively foster patient engagement through interactive digital tools. Policies should also ensure reliable internet infrastructure and tailor interventions to regional and sociodemographic contexts to improve overall health outcomes.